A perovskite-based composite material for humidity sensor and its preparation method and application

Through the combination of perovskite-based composite materials and hollow mesoporous silica, the problems of complex preparation process and unstable performance of perovskite humidity sensor materials are solved, and high sensitivity and stable humidity detection effects are achieved.

CN119331620BActive Publication Date: 2025-02-28BIOGENOUS BIOTECH INC +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411885196.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The preparation process of existing perovskite humidity sensor materials is complex, has high cost, and is difficult to control the particle size, resulting in unstable performance and complex humidity signals, making them difficult to extract.

Method used

Perovskite-based composite materials, including Cs2NaBiCl6:xTm3+/zYb3+@mSiO2 or Cs2NaTbCl6:xTm3+/zYb3+@mSiO2, are used to control particle size and performance through a specific mixing and drying process, combined with hollow mesoporous silica.

Benefits of technology

It realizes high sensitivity humidity detection of perovskite-based composite materials, with good stability and a wide range of applications, including humidity detection and fluorescence imaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the field of humidity sensor devices. The invention discloses a perovskite-based composite material for humidity sensor and a preparation method and application thereof. The molecular formula of the perovskite-based composite material is Cs2NaBiCl6:xTm 3+ / zYb 3+ @mSiO2 or Cs2NaTbCl6:xTm 3+ / zYb 3+ @mSiO2. The perovskite-based composite material of the present invention has a blue light emission peak at 456nm under an excitation wavelength of 980nm; and has a violet light emission peak at 394nm under an excitation wavelength of 254nm. The perovskite-based composite material of the present invention can respond to water, and the emission intensity is linearly related to the reaction time, and humidity monitoring and fluorescence imaging can be realized. The preparation process is simple and the cost is low, which is conducive to industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of humidity sensor devices and relates to a perovskite-based composite material for a humidity sensor and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Currently, nanoprobes have been used in many aspects of daily life. Among them, perovskite humidity sensors have the characteristics of high sensitivity and fast response, and can accurately detect changes in humidity in a short time, so they have received widespread attention. However, the preparation process of some perovskite materials used in humidity sensors is complicated, the cost is high, and the particle size and performance are difficult to accurately control, resulting in differences in the performance of nano humidity sensors produced in different batches. At the same time, there are also problems such as the signals generated by nanomaterial humidity sensors are relatively complex and humidity information is difficult to extract. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a perovskite-based composite material for a humidity sensor and a preparation method and application thereof. The perovskite-based composite material prepared by the present invention can accurately detect changes in humidity and has good stability, solving the problems of complex preparation process, high cost, difficult control of particle size and complex humidity measurement signals of existing perovskite materials.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] In a first aspect of the present invention, a perovskite-based composite material for a humidity sensor is provided, comprising: the molecular formula of the perovskite-based composite material is Cs2NaBiCl6:xTm 3+ / zYb 3+ @mSiO2 or Cs2NaTbCl6:xTm 3+ / zYb 3+ @mSiO2, where x is 0.09-0.1, z is 0.9-1, mSiO2 (hollow mesoporous silica) and Cs2NaBiCl6:xTm 3+ / zYb 3+ or Cs2NaTbCl6:xTm 3+ / zYb 3+ The mass ratio is 0.4:(0.963-0.101).

[0007] A second aspect of the present invention provides a method for preparing the above-mentioned perovskite-based composite material for a humidity sensor, comprising:

[0008] Cesium chloride, sodium chloride, M salt, thulium chloride, and ytterbium chloride are mixed, and then hydrochloric acid solution and water are added to react. After the reaction is completed, a double perovskite solution is obtained;

[0009] The hollow mesoporous silica is added to the double perovskite solution, mixed evenly, and vacuum dried to obtain a perovskite-based composite material;

[0010] Wherein, the M salt is bismuth chloride or terbium chloride.

[0011] In order to make the hollow mesoporous silica and the double perovskite material mix evenly, the present invention studies the mixing process. Preferably, the specific steps of mixing the hollow mesoporous silica and the double perovskite solution are: first stirring for 30min-60min, and then ultrasonicating for 15min-20min.

[0012] The vacuum drying has high efficiency, which not only saves time, but also improves the quality of the composite material and reduces the loss rate of the composite material. Therefore, the present invention studies the drying temperature, and preferably, the vacuum drying temperature is 60°C-65°C.

[0013] The study found that if the vacuum drying time is too long, the energy consumption is high and the loss rate of the composite material increases; if the vacuum drying time is too short, moisture remains in the composite material, affecting its fluorescence properties and humidity detection effect. Therefore, the present invention studies the vacuum drying time. Preferably, the vacuum drying time is 2-3 days.

[0014] The purity of the perovskite-based composite material will affect its fluorescence characteristics and humidity detection effect. Therefore, preferably, the method further includes: purifying the perovskite-based composite material.

[0015] In order to achieve a better purification effect, the present invention studies the purification process of the perovskite-based composite material. Preferably, the specific conditions of the purification include: mixing the perovskite-based composite material with water, ultrasonicating for 5min-8min, centrifuging once, taking the supernatant, centrifuging again, and collecting the precipitate.

[0016] In order to allow the perovskite-based composite material to remain in the supernatant, the present invention studies the rotation speed and time of a centrifugation. Preferably, the centrifugation condition is 4500r / min-5000r / min for 4min-5min.

[0017] In order to allow the perovskite-based composite material to precipitate, the present invention studies the rotation speed and time of the secondary centrifugation. Therefore, preferably, the secondary centrifugation condition is centrifugation at 12000r / min-13000r / min for 10min-15min.

[0018] The third aspect of the present invention provides the use of the above-mentioned perovskite-based composite material for humidity sensor in humidity detection.

[0019] Beneficial effects of the present invention

[0020] (1) The perovskite-based composite material prepared by the present invention can respond to water, and the emission intensity is linearly related to the reaction time. It can be used not only in humidity detection, but also in the fields of fluorescence imaging, and has a wide range of applications.

[0021] (2) The perovskite-based composite material prepared by the present invention can realize fluorescence emission of different colors (blue light or purple light) under the excitation of different wavelengths of excitation light (980nm, 254nm), and has fluorescence imaging function.

[0022] (3) The perovskite-based composite material provided by the present invention has a small particle size, a simple detection method, and can improve industrial detection efficiency;

[0023] (4) The perovskite-based composite material provided by the present invention has a simple preparation process and low cost. The hollow mesoporous structure of silica can control the particle size of double perovskite, and the double perovskite can be removed by long-term water washing, thereby achieving the reuse of silica, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention, and do not constitute improper limitations on the present invention.

[0025] Figure 1 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ SEM images of nanoparticles;

[0026] Figure 2 It is Cs2NaBiCl6:Tm prepared in Example 1 of the present invention 3+ / Yb 3+ Emission spectra of nanoparticles;

[0027] Figure 3 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @mSiO2 nanoparticles water response diagram;

[0028] Figure 4 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+@ Linear plot of water response of mSiO2 nanoparticles;

[0029] Figure 5 is a scanning electron microscope image of the hollow mesoporous silica prepared in Example 2 of the present invention;

[0030] Figure 6 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @SEM image of mSiO2;

[0031] Figure 7 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @mSiO2 and emission spectra of mSiO2;

[0032] Figure 8 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @Transmission electron microscope (TEM) image of mSiO2;

[0033] Fig. 9 It is Cs2NaBiCl6:Tm prepared in Examples 1, 2 and 3 of the present invention. 3+ / Yb 3+ Nanoparticles, mSiO2, Cs2NaBiCl6:Tm 3+ / Yb 3+ @X-ray diffraction pattern of mSiO2;

[0034] Fig.10 It is Cs2NaTbCl6:Tm prepared in Example 4 of the present invention 3+ / Yb 3+ @mSiO2 emission spectrum;

[0035] Fig.11 It is Cs2NaTbCl6:Tm prepared in Example 4 of the present invention 3+ / Yb 3+ @Fluorescence imaging of mSiO2 nanoparticles.

[0036] Fig.12 It is Cs2NaTbCl6:Tm prepared in Example 4 of the present invention 3+ / Yb 3+ @MSiO2 nanoparticle bioimaging bright field image.

[0037] Fig.13 It is Cs2NaTbCl6:Tm prepared in Example 4 of the present invention 3+ / Yb 3+@mSiO2 nanoparticle biological imaging dark field image.

[0038] Fig.14 It is Cs2NaTbCl6:Tm prepared in Example 4 of the present invention 3+ / Yb 3+ @mSiO2 nanoparticle biological imaging bright and dark field overlay. DETAILED DESCRIPTION

[0039] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0040] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0041] The present invention has no particular limitation on the sources of the reagents in the examples, and commercially available products known to those skilled in the art may be used.

[0042] Example 1

[0043] This example provides Cs2NaBiCl6:Tm 3+ / Yb 3+ 、Cs2NaTbCl6:Tm 3+ / Yb 3+ The preparation comprises the following steps:

[0044] (1) Weigh 2 mmol of cesium chloride, 1 mmol of sodium chloride, and 1 mmol of bismuth chloride (or terbium chloride) into a beaker, add 0.9 mmol of YbCl3 and 0.09 mmol of TmCl3, add 6 mL of 36% concentrated hydrochloric acid and 20 mL of water, and stir until the solution is clear.

[0045] (2) Place the clear solution in a drying oven at 60°C for 24 hours to obtain a yellow solid, which is then ground into powder.

[0046] Determine the obtained Cs2NaBiCl6:Tm 3+ / Yb 3+ SEM images of nanoparticles, such as Figure 1 As shown. Figure 1 It can be seen that Cs2NaBiCl6:Tm 3+ / Yb 3+ In flake form.

[0047] Cs2NaBiCl6:Tm 3+ / Yb 3+The XRD pattern of the nanoparticles is completely consistent with the standard card (PDF#77-1831), such as Fig. 9 As shown, the prepared Cs2NaBiCl6:Tm 3+ / Yb 3+ The nanoparticles are pure phase and do not have any impurities.

[0048] Take part of the powder to determine Cs2NaBiCl6:Tm 3+ / Yb 3+ The emission spectrum of Figure 2 As shown, the emission peak is at 456nm, the excitation light source used is 980nm, and the power is 1.2W.

[0049] At the same time, this embodiment also prepared Cs2NaTbCl6:Tm 3+ / Yb 3+ Nanoparticles.

[0050] Example 2

[0051] This embodiment provides a preparation method of hollow mesoporous silica (mSiO2), comprising the following steps:

[0052] (1) Add 2 g CTAC (cetyltrimethylammonium chloride), 0.1 mL TEA (triethanolamine) and 20 mL water to a flask, heat to 80°C, and stir until the solution becomes clear.

[0053] (2) Add 1 mL of TEOS (tetraethyl orthosilicate) to the flask in step (1) and react for 1 h.

[0054] (3) Mix BTESE (bistriethoxysilane ethane) and TEOS in a volume ratio of 1:1 to obtain a silica precursor. Add 2 mL of silica precursor to the flask in step (2), react for 3 h, and then wash with 20 mL of ethanol 2 to 3 times to obtain a precipitate.

[0055] (4) Dissolve 0.15 g of ammonium nitrate in 20 mL of ethanol until the ammonium nitrate is completely dissolved, then pour it into the above precipitate, sonicate until there is no obvious precipitation, heat to 60 °C for 2 h, wash off the CTAC, and repeat the above steps 3 times. Centrifuge at high speed to obtain a precipitate.

[0056] (5) Add a mixed solution of 30 mL of water and 3 mL of 26% ammonia water to the above precipitate, sonicate until there is no obvious precipitation, and then transfer the mixed solution to a 95°C oil bath for etching for 3 h.

[0057] (6) The solution after the reaction was centrifuged at 12000 r / min × 15 min to obtain hollow mesoporous silica, which was then washed with water and dried.

[0058] Figure 5 This is a scanning electron microscope image of the hollow mesoporous silica prepared in Example 2 of the present invention.

[0059] Example 3

[0060] This example provides Cs2NaBiCl6:Tm 3+ / Yb 3+ The preparation steps of @mSiO2 are as follows:

[0061] (1) Weigh 2 mmol of cesium chloride, 1 mmol of sodium chloride, and 1 mmol of bismuth chloride into a beaker, add 1 mmol of YbCl3 and 0.1 mmol of TmCl3, add 6 mL of concentrated hydrochloric acid (mass concentration is 36%) and 20 mL of water and stir until the solution is clear.

[0062] (2) 0.4 g of the hollow mesoporous silica powder prepared in Example 2 was added to the above solution, stirred for 60 min, ultrasonicated for 15 min, and vacuumed for 30 min, and then placed in a drying oven at 60° C. for 3 days.

[0063] (3) Add 20 mL of water, sonicate for 5 min, centrifuge (4500 r / min × 5 min), take the supernatant (containing small particles), centrifuge (13000 r / min × 10 min), and obtain the precipitate Cs2NaBiCl6:Tm 3+ / Yb 3+ @mSiO2.

[0064] Figure 6 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @SEM image of mSiO2;

[0065] Figure 7 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @mSiO2 emission spectrum;

[0066] Figure 8 It is Cs2NaBiCl6:Tm prepared in Example 3 of the present invention 3+ / Yb 3+ @Transmission electron microscope (TEM) image of mSiO2.

[0067] Example 4

[0068] This example provides Cs2NaTbCl6:Tm 3+ / Yb 3+ The preparation steps of @mSiO2 are as follows:

[0069] (1) Weigh 2 mmol of cesium chloride, 1 mmol of sodium chloride, and 1 mmol of terbium chloride into a beaker, add 1 mmol of YbCl3 and 0.1 mmol of TmCl3, add 6 mL of concentrated hydrochloric acid (mass concentration is 36%) and 20 mL of water and stir until the solution is clear.

[0070] (2) 0.4 g of the hollow mesoporous silica powder prepared in Example 2 was added to the above solution, stirred for 30 min, ultrasonicated for 20 min, and vacuumed for 35 min, and then placed in a drying oven at 65° C. for 2 days.

[0071] (3) Add 20 mL of water, sonicate for 8 min, centrifuge (5000 r / min × 4 min), take the supernatant (containing small particles), centrifuge (12000 r / min × 15 min), and obtain the precipitate Cs2NaTbCl6:Tm 3+ / Yb 3+ @mSiO2.

[0072] Fig.10 It is Cs2NaTbCl6:Tm prepared in Example 4 of the present invention 3+ / Yb 3+ @Emission spectrum of mSiO2.

[0073] Application Example 1

[0074] The Cs2NaBiCl6:Tm prepared in Example 3 3+ / Yb 3+ @mSiO2 is used for humidity monitoring. The specific steps are as follows:

[0075] (1) Take 0.3g Cs2NaBiCl6:Tm 3+ / Yb 3+ @mSiO2 nanoparticles were placed in 10mL of water and stirred for different times (1h~12h);

[0076] (2) Under 980nm laser irradiation, Cs2NaBiCl6:Tm was tested using a spectrometer 3+ / Yb 3+ @mSiO2 nanoparticles fluorescence spectrum, the fluorescence spectrum with humidity curve is obtained, and then the humidity in the environment of the composite material can be calculated using this curve, such as Figure 3 and Figure 4 As shown, the excitation light source used is 980nm and the power is 1.2W. The above results show that: Cs2NaBiCl6:Tm 3+ / Yb 3+ @mThe longer SiO2 reacts with water, the lower the fluorescence emission intensity.

[0077] Application Example 2

[0078] The Cs2NaTbCl6:Tm prepared in Example 4 3+ / Yb 3+ @mSiO2 is used in fluorescence imaging experiments. The specific steps are as follows:

[0079] (1) Weigh 0.1 g of polyvinyl alcohol and add 5 mL of Cs2NaTbCl6:Tm 3+ / Yb 3+ @mSiO2 aqueous solution (mass concentration of 3%) was stirred evenly to obtain a viscous colloid.

[0080] (2) Prepare appropriate cardboard, cover the hollow pattern of appropriate size, apply the colloid obtained above, dry and remove the hollow pattern to obtain the corresponding pattern. Fig.11 Cs2NaTbCl6:Tm prepared in Example 4 3+ / Yb 3+ @mSiO2 luminescence pattern, the excitation light source used is 254nm.

[0081] Application Example 3

[0082] The Cs2NaTbCl6:Tm prepared in Example 4 3+ / Yb 3+ @mSiO2 is used in biological imaging experiments. The specific steps are as follows:

[0083] (1) HuH-7 hepatoma cells were cultured at 1×10 5 The density of cells was placed in a 6-well plate. After 24 h, Cs2NaTbCl6:Tm 3+ / Yb 3+ @mSiO2 nanoparticles (10 μM) were added to the wells and incubated with the cells for 6 h.

[0084] (2) The cells were washed three times with phosphate buffered saline (PBS) (pH 7.2-7.4), and bright field and fluorescence imaging of liver cancer cells were performed using the bright field and UV channels of an inverted fluorescence microscope, respectively.

[0085] Fig.12 Cs2NaTbCl6:Tm prepared in Example 4 3+ / Yb 3+ @MSiO2 and liver cancer cell HuH-7 incubated in bright field images, Fig.13 For dark field imaging, Fig.14 This is an overlay of bright and dark field imaging.

[0086] It can be seen that the Cs2NaTbCl6:Tm prepared by the present invention 3+ / Yb 3+@mSiO2 can be used for fluorescence imaging.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An application of a perovskite-based composite material for a humidity sensor in humidity detection, characterized in that: include: The molecular formula of the perovskite-based composite material is Cs2NaBiCl6:xTm 3+ / zYb 3+ @mSiO2, where x is 0.09-0.1, z is 0.9-1, mSiO2 and Cs2NaBiCl6:xTm 3+ / zYb 3+ The mass ratio is 0.4:(0.963-0.101).

2. The use according to claim 1, characterized in that The preparation method of the perovskite-based composite material for a humidity sensor comprises: Cesium chloride, sodium chloride, M salt, thulium chloride, and ytterbium chloride are mixed, and then hydrochloric acid solution and water are added to react. After the reaction is completed, a double perovskite solution is obtained; The hollow mesoporous silica is added to the double perovskite solution, mixed evenly, and vacuum dried to obtain a perovskite-based composite material; Wherein, the M salt is bismuth chloride.

3. The use according to claim 2, characterized in that The specific steps of mixing the hollow mesoporous silica with the double perovskite solution are: first stirring for 30 minutes to 60 minutes, and then ultrasonicating for 15 minutes to 20 minutes.

4. The use according to claim 2, characterized in that The vacuum drying temperature is 60°C-65°C.

5. The use according to claim 2, characterized in that The vacuum drying time is 2-3 days.

6. The use according to claim 2, characterized in that Also includes: The perovskite-based composite material is purified.

7. The use according to claim 6, characterized in that The specific conditions of the purification include: mixing the perovskite-based composite material with water, ultrasonicating for 5 minutes to 8 minutes, centrifuging once, taking the supernatant, centrifuging twice, and collecting the precipitate.

8. The use according to claim 7, characterized in that The condition of the one centrifugation is centrifugation at 4500r / min-5000r / min for 4min-5min.

9. The use according to claim 7, characterized in that The secondary centrifugation condition is centrifugation at 12000 r / min-13000 r / min for 10 min-15 min.

Citation Information

Patent Citations

  • Halide perovskite nanocrystal, composite material thereof, preparation method and application

    CN114836209A

  • Luminescent composite nano-material, preparation method thereof and application of luminescent composite nano-material in anti-counterfeiting or temperature sensing

    CN118995220A